Beneficial effects of Apelin-13 on metabolic diseases and exercise - Wen, Ruiming; Huang, Ruiqi; Xu, Ke; Cheng, Yang; Yi, Xuejie (Frontiers in Endocrinology, 2023)
Apelin, a novel endogenous ligand of the G-protein-coupled receptor APJ, is encoded by the APLN gene and can be hydrolyzed into multiple subtypes, with Apelin-13 being one of the most active subtypes of the Apelin family. Recent studies have revealed that Apelin-13 functions as an adipokine that participates in the regulation of different biological processes, such as oxidative stress, inflammation, apoptosis, and energy metabolism, thereby playing an important role in the prevention and treatment of various metabolic diseases. However, the results of recent studies on the association between Apelin-13 and various metabolic states remain controversial. Furthermore, Apelin-13 is regulated or influenced by various forms of exercise and could therefore be categorized as a new type of exercise-sensitive factor that attenuates metabolic diseases. Thus, in this review, our purpose was to focus on the relationship between Apelin-13 and related metabolic diseases and the regulation of response movements, with particular reference to the establishment of a theoretical basis for improving and treating metabolic diseases.